How does socio-economic position (SEP) get biologically embedded? A comparison of allostatic load and the epigenetic clock(s). (June 2019) - McCrory, Cathal; Fiorito, Giovanni; Ni Cheallaigh, Cliona; Polidoro, Silvia; Karisola, Piia; Alenius, Harri; Layte, Richard; Seeman, Teresa; Vineis, Paolo; Kenny, Rose Anne
Highlights: Low socio-economic position (SEP) is linked with earlier morbidity and mortality. Researchers have debated how the social environment gets biologically embedded. Epigenetic age acceleration and allostatic load are two potential candidates. Allostatic load was strongly socially patterned by SEP in adult life. The epigenetic clock measures were not strongly pattered by SEP. Abstract: Individuals of lower socio-economic position (SEP) carry a heavier burden of disease and morbidity and live shorter lives on average compared with their more advantaged counterparts. This has sparked research interest in the processes and mechanisms via which social adversity gets biologically embedded. The present study directly compares the empirical worth of two candidate mechanisms: Allostatic Load (AL) and the Epigenetic Clock(s) for advancing our understanding of embodiment using a sub-sample of 490 individuals from the Irish Longitudinal Study (TILDA) who were explicitly selected for this purpose based on their inter-generational life course social class trajectory. A battery of 14 biomarkers representing the activity of 4 different physiological systems: Immunological, Cardiovascular, Metabolic, and Renal was used to construct the AL score. Biomarkers were dichotomised into high and low risk groups according to sex-specific quartiles of risk and summed to create a count ranging from 0-14. Three measures of epigenetic age acceleration were computed according to three sets of age-associated Cytosine-phosphate-Guanine (CpG) sites described by Horvath, Hannum and Levine. AL was strongly socially patterned across a number of measures of SEP, while the epigenetic clocks were not. AL partially mediated the association between measures of SEP and an objective measure of physiological functioning: performance on the Timed Up and Go (TUG test). We conclude that AL may represent the more promising candidate for understanding the pervasive link between SEP and health.